Evaluation of impacts of the occupation, compatibility and adequacy process applied to buildings in residential yards on the construction site code of Palmas city – Tocantins state (TO). - Amorim, Rafael Alves; Parente, Dênis Cardoso; Pizzio, Alex; Aparecida da Rocha Silva, Mônica (Revista Nacional de Gerenciamento de Cidades, 2022)
The aim of the present study is to evaluate the progress of the occupation process applied to residential yards of Palmas City – Tocantins State (TO) in the light of the legislation providing on parameters and guidelines for residential buildings in this municipality. Aerial and satellite images, as well as tools of the geographic information system (GIS), at high resolution standards, were used for data processing and collection. Study site encompassed yards 407 North, 504 South and the Bertaville Sector, which are located in different regions of the city and at different occupation stages. Seeking to attest to the potential of the generated products in terms of photointerpretation, Geometric and geographic accurate measurements were turned into field images in order to attest to the photo-interpretation potential of the generated products. Impacts of rainwater surface runoff on the study site were evaluated based on urban index data, occupancy rate, built-up areas, waterproofing rates and urban voids, confronted with construction site code provisions.